2011
DOI: 10.1016/s1995-7645(11)60180-6
|View full text |Cite
|
Sign up to set email alerts
|

In vitro total phenolics, flavonoids contents and antioxidant activity of essential oil, various organic extracts from the leaves of tropical medicinal plant Tetrastigma from Sabah

Abstract: The findings show that the extent of antioxidant activity of the essential oil and all extracts are in accordance with the amount of phenolics present in that extract. Leaves of Tetrastigma being rich in phenolics may provide a good source of antioxidant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
74
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(84 citation statements)
references
References 11 publications
6
74
0
4
Order By: Relevance
“…The present study, the total flavonoids contents of the different organic crude plant extracts were determined by Hossain et al method that are reported as quercetin equivalents [16] . Among the five crude extracts from T. vulgaris, methanol extract was containing highest amount of flavonoids content compounds followed by butanol>chloroform>ethyl acetate>hexane crude extract.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The present study, the total flavonoids contents of the different organic crude plant extracts were determined by Hossain et al method that are reported as quercetin equivalents [16] . Among the five crude extracts from T. vulgaris, methanol extract was containing highest amount of flavonoids content compounds followed by butanol>chloroform>ethyl acetate>hexane crude extract.…”
Section: Discussionmentioning
confidence: 97%
“…All these secondary metabolites components showed antioxidant and antimicrobial properties through different mechanism. Normally these secondary metabolites components were isolated from the polar plant extract [16] . The phytochemical screening of hexane, ethyl acetate, chloroform, butanol, methanol crude extracts from dry powder leaves samples of T. vulgaris used in this present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance lupeol, α amyrin, olcanolic, and ursolic acids [21] . The flower of A. ilicifolius contained saponin and triterpenoidal saponin and these compounds have been found in the root of A. ilicifolius [27][28][29][30][31] . Tiwara et al [32] and Huo et al [33] reported that A. ilicifolius mangrove contained alkaloids i.e.…”
Section: Discussionmentioning
confidence: 99%